SOME REFLECTIONS ON THE USE OF INTERDISCIPLINARY COMMUNICATION IN MATHEMATICS EDUCATION (Multidisciplinary Journal of Science and Technology, 2024)
Interdisciplinary communication is increasingly recognized as a key component in modern education, where subjects are interconnected, and real-world applications demand a blending of knowledge from multiple fields. Mathematics, often perceived as an isolated or abstract discipline, can greatly benefit from interdisciplinary approaches that integrate concepts from sciences, arts, and social sciences. This paper explores how interdisciplinary communication enriches mathematics education by fostering a more comprehensive understanding, enhancing student engagement, and developing critical thinking skills. By examining practical strategies and case studies, this article seeks to shed light on the transformative potential of interdisciplinary collaboration in mathematics education.